(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article discusses the issues of the formation of the Kyrgyz national terminology. The article includes statements by academician B.O.Oruzbaeva about the history and formation of Kyrgyz terminology. The work also reflects the great contribution to the foundation and formation of national terminology by Kasym Tynystanov, a scientist who was one of the first to conduct research in this direction. New words that have appeared in the Kyrgyz language, especially terms, are not only socio-political in nature, but also relate to various branches of science, which led to the formation of Kyrgyz lexicography, including translation theory.